Covid-19 supply chain disruptions and their consequences on the Volkswagen group - Vašíčková, Tereza (2025)
The COVID-19 pandemic significantly disrupted global supply chains, challenging businesses across all sectors, including the automotive industry. This Bachelor Thesis examines the short-term and long-term impacts of these disruptions on the Volkswagen Group's strategies. It focuses on challenges such as revenue losses, increased costs, and production halts, particularly due to semiconductor shortages. The thesis also highlights Volkswagen’s financial, social, and innovative strategies to mitigate these challenges and adapt to an evolving economic landscape.